Nanotechnology: A Novel Tool To Enhance The Bioavailability Of Micronutrients (Journal of Pharmaceutical Negative Results, 2022)
Nutraceuticals, diagnostics, therapeutics, pharmaceuticals, and food systems have all been transformed by nanotechnology. The solution to increasing the bioavailability of oral delivery of bioactive compounds is largely dependent on nanoparticles. This review showed that nanoparticles can make micronutrients like vitamin B12, vitamin A, folic acid, and iron more bioavailable. After taking nano-based supplements, the toxicity of nanoparticle-based delivery systems remains a major concern. A major gap in the field of nanoceuticals is the mode of the mechanism of nanomaterials and bioactive components in various physiological conditions of the human body. In order to confirm the precise approach to physiological changes in the human body, further clinical investigations based on evidence are required in the future.